Dental Poly(methyl methacrylate)-Based Resin Containing a Nanoporous Silica Filler - Kentaro Hata; Hiroshi Ikeda; Yuki Nagamatsu; Chihiro Masaki; Ryuji Hosokawa; Hiroshi Shimizu (Journal of Functional Biomaterials, 2022)
Poly(methyl methacrylate) (PMMA)-based resins have been conventionally used in dental prostheses owing to their good biocompatibility. However, PMMA-based resins have relatively poor mechanical properties. In the present study, a novel nanoporous silica filler was developed and introduced into PMMA-based resins to improve their mechanical properties. The filler was prepared by sintering a green body composed of silica and an organic binder, followed by grinding to a fine powder and subsequent silanization. The filler was added to photocurable PMMA-based resin, which was prepared from MMA, PMMA, ethylene glycol dimethacrylate, and a photo-initiator. The filler was characterized by scanning electron microscopy (SEM), X-ray diffraction analysis, nitrogen sorption porosimetry, and Fourier transform infrared (FT-IR) spectroscopy. The PMMA-based resins were characterized by SEM and FT-IR, and the mechanical properties (Vickers hardness, flexural modulus, and flexural strength) and physicochemical properties (water sorption and solubility) were evaluated. The results suggested that the filler consisted of microparticles with nanopores. The filler at 23 wt % was well dispersed in the PMMA-based resin matrix. The mechanical and physicochemical properties of the PMMA-based resin improved significantly with the addition of the developed filler. Therefore, such filler-loaded PMMA-based resins are potential candidates for improving the strength and durability of polymer-based crown and denture base.